Assessing health and safety practice for refurbishment work at Klang Valley / Muhammad Muzakkir Ismail - Ismail, Muhammad Muzakkir (Faculty of Architecture, Planning and Surveying, 2015)
Health and safety issues have always been a major problem and concern in construction industry. Wherever reliable records are available, refurbishment work is one of the most dangerous on health and safety criteria, particularly in developing countries. Refurbishment is any upgrade, alteration, modification, adaptation, and extension in the current status of the building to improve building performance and efficiency of the building structure. Refurbishment project is more difficult to monitor and coordinate compare with new construction. The main problem faced for refurbishment work in Malaysia is increasing accident and fatalities cases, in 2014 at Johor Bharu state 56 workers died due to falling from height. To overcome this problem, with following the comprehensive health and safety practice from Department of Occupational Health and Safety (DOSH) regulation the probability accident happen in refurbishment project is small and minimize the potential hazard in refurbishment work. Furthermore, with providing health and safety training and education towards workers will minimize the potential hazards in refurbishment project. Research aim of this dissertation is to identify the best current health and safety practice in refurbishment work. To achieve the aim of this research fourth research objectives were outlined. The objective are to study the current health and safety practice, identify potential hazards, evaluate the level awareness among workers, and propose a recommendation in improving health and safety practice for refurbishment work has been identified and reviewed by author. Research method that use to achieve four objective above first through semi-structured interviewed to study the current health and safety practice, to identify potential hazards and propose a recommendation in improving health and safety practice. The questionnaire distribution has been made in case study to evaluate the level of awareness among worker towards health and safety practice in refurbishment project. The final result was noted on the analysis and finding of this research. Based on the three (3) case study above author indicate Dewan Bahasa dan Pustaka (case study 1) use current practice from Jabatan Kerja Raya (JKR). Case studies at Summit Subang USJ (case study 2) and Bangsar Trade Centre (case study 3) use follow practice from Department Occupational Safety and Health (DOSH).